(untitled) (Sociologisk Forskning, 1993)
The welfare state and compulsory heterosexuality The welfare state has been scrutinized from different angles. Here the author tries to show how the welfare state enforces heterosexuality as a norm for the good life. Welfare reforms regarding family law, adoption, insemination, and some social insurances, are discussed. Sweden and Denmark are used for comparison, since Denmark is the only country in the world which gives homosexuals right to civil marriage. This civil marriage has a special name: partnership (partnerskap). One question that can be asked is if partnership challanges the norm of heterosexuality since lesbian and gay lives are accepted by the state. But there is a similarity as well as a difference between the laws regarding equality between the sexes (jämställdhet) and the laws regarding homosexuals. In the first case it is man who is the norm for the good life and women are given the same rights as men. In the second case it is the heterosexuals who are the norm for the good life but homosexuals are only given some of their rights.